Accumulating evidence for a role of TCF7L2 variants in bipolar disorder with elevated body mass index. (2nd March 2016) - Cuellar‐Barboza, Alfredo B; Winham, Stacey J; McElroy, Susan L; Geske, Jennifer R; Jenkins, Gregory D; Colby, Colin L; Prieto, Miguel L; Ryu, Euijung; Cunningham, Julie M; Frye, Mark A; Biernacka, Joanna M
Abstract : Objectives: Bipolar disorder (BD) is a complex disease associated with various hereditary traits, including a higher body mass index (BMI). In a prior genome‐wide association study, we found that BMI modified the association of rs12772424 – a common variant in the gene encoding transcription factor 7‐like 2 ( TCF7L2 ) – with risk for BD. TCF7L2 is a transcription factor in the canonical Wnt pathway, involved in multiple disorders, including diabetes, cancer and psychiatric conditions. Here, using an independent sample, we evaluated 26 TCF7L2 single nucleotide polymorphisms (SNPs) to explore further the association of BD with the TCF7L2 –BMI interaction. Methods: Using a sample of 662 BD cases and 616 controls, we conducted SNP‐level and gene‐level tests to assess the evidence for an association between BD and the interaction of BMI and genetic variation in TCF7L2 . We also explored the potential mechanism behind the detected associations using human brain expression quantitative trait loci (eQTL) analysis. Results: The analysis provided independent evidence of an rs12772424–BMI interaction (p = 0.011). Furthermore, while overall there was no evidence for SNP marginal effects on BD, the TCF7L2 –BMI interaction was significant at the gene level (p = 0.042), with seven of the 26 SNPs showing SNP–BMI interaction effects with p < 0.05. The strongest evidence of interaction was observed for rs7895307 (p = 0.006). TCF7L2 expression showed a significant enrichment of association with the expression of other genes in the Wnt canonical pathway. Conclusions: The current study provides further evidence suggesting that TCF7L2 involvement in BD risk may be regulated by BMI. Detailed, prospective assessment of BMI, comorbidity, and other possible contributing factors is necessary to explain fully the mechanisms underlying this association.